Battle of the Band Names: The Best and Worst Band Names Ever (and All the Brilliant, Colorful, Stupid Ones in Between) - Bull Bart (Abrams Image, 2009)
Award-winning veteran music journalist Bart Bull has created a one-of-a-kind book and compiled hundreds of the most colorful, clever, obscure, and unusual band names of the past 50 years. Broken down into 35 highly designed chapters, Bull covers the worlds of Ska, Surf, Hip-Hop, Punk, Country, and Heavy Metal alongside more creative categories such as Tribute Bands, Girl Groups, Japanese Bands with English Names, and, most daringly, the Best and Worst band names of all time. The book’s free-styling flow is irresistible as one band name trips gracelessly over another from Sublime to The Ridiculous Poodles and on to The Ultimate Spinach. This jam-packed musical stream of consciousness is a perfect gift for music or language lovers as well as fans of cutting-edge graphic design.